Valorization of Agro-Waste for Wastewater Treatment: Adsorption of RY3 Dye Using Nut Shell Activated Carbon - Taşar, Şeyda; Kardaş, Elif; Kaya, Fatih; Yılgın, Melek; Duranay, Neslihan (My University, 2025)
In this study, the potential of using activated carbon (NSAC) obtained from nut shell as an adsorbent as a cost-effective and environmentally friendly material for removing Reactive Yellow 3 (RY3) dye from synthetic aqueous solutions by adsorption was evaluated. In producing nut shell-based activated carbon, a chemical activation method was used and NaOH was selected as the chemical agent. After chemical pretreatment, it was subjected to a carbonization process at 600 °C. The obtained activated carbon was analyzed using FTIR, SEM, and pHzpc techniques. Adsorption experiments were carried out under varying adsorption conditions. The effect of adsorption parameters was evaluated. The parameters and their ranges whose effects were evaluated in the study were; contact time (0-180 min), pH (4-11), temperature (298-328 K), dye concentration (25-100 mg/L), and adsorbent dose (10-45 mg/L). The best removal efficiency, 90.83%, and adsorption capacity of 272.5 mg/g were obtained at 328 K, pH 7.0, dye concentration of 75 mg/L, and adsorbent dose of 25 mg/L. The adsorption kinetics were found to be in good agreement with the pseudo-second-order model expressed as chemisorption. Langmuir isotherm analysis confirmed monolayer adsorption. These findings suggest that NSAC produced from agricultural wastes can be a sustainable alternative adsorbent in wastewater treatment applications.
Keywords: Adsorption; Characterization; activated carbon; Nutshell; Reactive Yellow 3